[18F]Fluoropyridine‐losartan: A new approach toward human Positron Emission Tomography imaging of Angiotensin II Type 1 receptors. (1st February 2023) - Abreu Diaz, Aida Mary; Rodriguez Riera, Zalua; Lee, Yanick; Esteves, Luis Miguel; Normandeau, Charles‐Olivier; Fezas, Baptiste; Hernandez Saiz, Alejandro; Tournoux, François; Juneau, Daniel; DaSilva, Jean N.
Abstract : Angiotensin II type 1 receptors (AT1 R) blocker losartan is used in patients with renal and cardiovascular diseases. [ 18 F]fluoropyridine‐losartan has shown favorable binding profile for quantitative renal PET imaging of AT1 R with selective binding in rats and pigs, low interference of radiometabolites and appropriate dosimetry for clinical translation. A new approach was developed to produce [ 18 F]fluoropyridine‐losartan in very high molar activity. Automated radiosynthesis was performed in a three‐step, two‐pot, and two‐HPLC‐purification procedure within 2 h. Pure [ 18 F]FPyKYNE was obtained by radiofluorination of NO2 PyKYNE and silica‐gel‐HPLC purification (40 ± 9%), preventing the formation of nitropyridine‐losartan in the second step. Conjugation with trityl‐losartan azide via click chemistry, followed by acid hydrolysis, C18‐HPLC purification and reformulation provided [ 18 F]fluoropyridine‐losartan in 11 ± 2% (decay‐corrected from [ 18 F]fluoride, EOB). Using tris[(1‐(3‐hydroxypropyl)‐1 H ‐1, 2, 3‐triazol‐4‐yl)methyl]‐amine (THPTA) as a Cu(I)‐stabilizing agent for coupling [ 18 F]FPyKYNE to the unprotected losartan azide afforded [ 18 F]fluoropyridine‐losartan in similar yields (11 ± 3%, decay‐corrected from [ 18 F]fluoride, EOB). Reverse‐phase HPLC was optimized by reducing the pH of the mobile phase to achieve complete purification and high molar activities (467 ± 60 GBq/μmol). The use of radioprotectants prevented tracer radiolysis for 10 h (RCP > 99%). The product passed the quality control testing. This reproducible automated radiosynthesis process will allow in vivo PET imaging of AT1 R expression in several diseases. Abstract : Automated radiosynthesis of [ 18 F]fluoropyridine‐losartan was improved by silica‐gel HPLC purification of [ 18 F]FPyKYNE, preventing the formation of nitropyridine‐losartan in the second step. Coupling with trityl‐protected or unprotected losartan azide, C18‐HPLC purification (pH 2), and reformulation (with radioprotectants) provided [ 18 F]fluoropyridine‐losartan in high molar activities (467 ± 60 GBq/μmol) and RCP > 99% for 10 h. The product passed the quality control testing accomplished in three validation runs according to the current requirements for PET radiotracers for human use.